A strategic management analysis for INSTEDT's nursing programme in a challenging environment / Syazliana Astrah Mohd Idris, Salamah Ani and Noor Azah Mohamed - Mohd Idris, Syazliana Astrah; Ani, Salamah; Mohamed, Noor Azah (2010)
Nurses are healthcare workers dedicated to treating and educating both individuals and communities. Due to government support, the private colleges take the opportunity to set up new nursing college including Institut Sains dan Teknologi Darul Takzim (INSTEDT) since 2006. The mushrooming of nursing private colleges across the Malaysia to cater the need of the demand of nurses' caused an increase in competition of student enrolment. It also may affect the quality of nursing student when the purpose of setting the nursing college mainly for profit oriented only. It will be difficult for those college which sincere in producing the quality nurses. The trend of set up new nursing college by other big company which is non academic and corporate organization such as Sime Darby, Bukit Merah and KPJ Healthcare, give an impact to INSTEDT's nursing programme. As a result, INSTEDT' s nursing programme faced declining number of student enrollment. Therefore, this applied business research (ABR) is aimed to analyze the INSTEDT's Nursing Programme through the strategic management concept so that it can generate new strategies in a challenging environment. We analyze current market condition for INSTEDT's nursing programme in nursing education industry with the concepts of Opportunities, Threats, EFE and Competitive Profile Matrix whereas, the resources and capability applied the Strengths and Weaknesses with IFE concept. The ABR further explore to generate, evaluate and select strategies including IE, TOWS, SPACE, Ansoff, Grand and QSPM Matrix.